Financial analysis of managing bamboo stands in a natural forest - Haron, Nor'ini; Mohamed, Azmy (Universiti Putra Malaysia Press, 1993)
This paper discusses the financial analysis of managing bamboo stands in natural forest. Throughout the analysis, actual costs incun-ed by the Forest Research Institute Malaysia (FRlM) in setting up trial plots in Kedah were studied. Results from the analysis show that the project is financially viable at a price ofRM 0.801culm provided that the project is financed at a lower interest rate. The project would be very attractive if bamboo culm could fetch a higher price or if yield could be improved.